2000
DOI: 10.1021/la000805k
|View full text |Cite
|
Sign up to set email alerts
|

Multiporphyrin Array from Interfacial Metal-Mediated Assembly and Its Langmuir−Blodgett Films

Abstract: The Cd2+-mediated assembly of multiporphyrin arrays at air−subphase interfaces has been studied. Surface pressure−area isotherms for the monolayers of zinc tetrapyridylporphyrin (ZnTPyP) showed that the mean ZnTPyP molecular area was 0.65 and 1.9 nm2 on water and 0.1 M Cd2+ subphase surfaces, respectively. Spectroscopic measurements indicated that absorption of the ZnTPyP Soret band was 11 nm redshifted in the monolayer of the Cd2+−ZnTPyP multiporphyrin array, but 23 nm redshifted in the ZnTPyP monolayer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 44 publications
7
59
0
1
Order By: Relevance
“…This may possibly be ascribed to the fact that the metal ions of Cd 2+ were coordinated with the carboxylated substituents (formation of a Cd-OOC coordination bond) of TCPP; as a result, the molecular interaction between the two porphyrin macrocycles was largely weakened. This phenomenon concurs with what we have previously observed in the metal-mediated multiporphyrin arrays [25,26], where it was revealed that the Soret band did not shift when the metal ions were coordinated with pyridyl substituents of the tetrapyridylporphyrin. Hence, we suggest that the TCPP macrocycles in the Cd-TCPP and Cd-TCPP/D-DBTarA LB films were arranged separately by the Cd 2+ ions, which weakened the porphyrin interaction and resulted in the absorption spectral feature similar to that in the dilute solutions (monomer).…”
Section: Page 8 Of 28supporting
confidence: 93%
See 1 more Smart Citation
“…This may possibly be ascribed to the fact that the metal ions of Cd 2+ were coordinated with the carboxylated substituents (formation of a Cd-OOC coordination bond) of TCPP; as a result, the molecular interaction between the two porphyrin macrocycles was largely weakened. This phenomenon concurs with what we have previously observed in the metal-mediated multiporphyrin arrays [25,26], where it was revealed that the Soret band did not shift when the metal ions were coordinated with pyridyl substituents of the tetrapyridylporphyrin. Hence, we suggest that the TCPP macrocycles in the Cd-TCPP and Cd-TCPP/D-DBTarA LB films were arranged separately by the Cd 2+ ions, which weakened the porphyrin interaction and resulted in the absorption spectral feature similar to that in the dilute solutions (monomer).…”
Section: Page 8 Of 28supporting
confidence: 93%
“…Previously, we found a significant increase in the average molecular area of monolayers of tetrapyridylporphyrin (TPyP) on the Cd 2+ subphase surface (from 0.6 nm 2 to nearly 2 nm 2 per TPyP) due to the formation of Cd-TPyP multiporphyrin arrays or coordination polymers [25,26]. In this case, such a phenomenon was not observed, indicating that although Cd-OOC coordination bonds could be formed at the interface, they may not lead to the formation of Cd 2+ -mediated two-dimensional multiporphyrin arrays or coordination polymers.…”
Section: Monolayers Of Tcpp and Its Mixtures With D-/l-dbtaramentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54][55][56][57][58][59] Qian et al employed a metal salt aqueous solution as a subphase and porphyrin molecules as the spreading substance. [54][55][56][57][58][59] The combination of functionalized porphyrin molecules such as 5,10,15,20-tetrakis(4-pyridyl)-21H,23H-porphyrin (H 2 TPyP) and its metal ion derivatives (MTPyP, M = Zn II , Mn III , TiO) with palladium salts was expected to lead to the formation of metal-mediated porphyrin arrays. [54][55][56][57] The specific combination of molecular building blocks was Eur.…”
Section: Methods For Preparing Langmuir-blodgett Filmsmentioning
confidence: 99%
“…Nevertheless, the two Q bands for ZnTPyP in DMF shift to a lower energy (561 and 608 nm) for the Cu-ZnTPyP micro-lumps in solution. These results suggest the formation of J-type aggregates with an edge-to-edge molecular arrangement in the micro-lumps of ZnTPyP [31]. Similarly, the self-assembled Cu-ZnTPyP micro-prisms were observed with a relatively weaker Soret band at 435 nm and a stronger Soret band at 470 nm as well as the red-shifted Q bands at 12 561 and 608 nm.…”
Section: Uv-vis Diffuse Reflectance Spectra (Drs)mentioning
confidence: 67%